The Law Politics in The Reformulation of Interfaith Marriage in Indonesia - Teti Hadiati; Makrum Makrum (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2020)
The issues explored in this study revolve around whether interfaith marriages align with the philosophical values of Indonesian marriage law, and why the validity of such marriages remains contentious in Indonesian legal context. In connection with the principle of ongoing legal conditions and public order, the implementation of marriage registration signifies a recognition of interfaith marriages, which the community accepts as a natural reality. This research employs both normative legal analysis and quantitative sociological research methods. The methodology evaluates matters concerning public order, legal compliance, and the continuation of existing legal situations or acquired rights. Based on this research, it was concluded that interfaith marriages are deemed inconsistent with the philosophical principles of Indonesian marriage law rooted in religious doctrine. Such marriages could potentially undermine the longstanding efforts in Indonesian marriage law legislation aimed at upholding public order. Consequently, registrations conducted by civil registry offices lack authoritative legal status and are merely administrative procedures.